BUNUH DIRI “ULAH PATI” DALAM SUSASTRA HINDU: Kajian Psikologi Agama - Sura Adnyana, Eka (Pangkaja: Jurnal Agama Hindu, 2025)
Bali ranks third with the most suicide cases in Indonesia with 638 cases, following Central Java and East Java. Suicide or often called "ulah pati" is seen as a very reprehensible act because it disrupts the process of karma and reincarnation. This paper uses the theory of religious psychology of K.I. Pargament combined with Ricoeur's Hermeneutics theory. Data are analyzed through the stages of data reduction, data presentation, and verification. The results of the analysis are then presented informally. Suicide as a phenomenon is often a reflection of spiritual emptiness, the absence of a deep understanding of the nature of life and religious values ​​that give meaning and direction. Ending life prematurely is considered inappropriate because it inhibits the spiritual process that is truly needed to achieve moksa. The act of suicide not only makes the self (spirit) get the torture of the darkness of hell for 60 thousand years and causes the surrounding environment to become dirty or tired. The impurity of the body for a person who kills himself is not worthy of a cremation ceremony, including the shedding of tears or sprinkling of water that must be offered to the Gods and making people carry the body (suicide corpse) in the cremation must do spiritual self-cleansing through the path of tapta kṛccha vratam and it is considered necessary to make efforts to prevent suicide strategies in the Hindu context.